2021
DOI: 10.1111/1759-7714.14169
|View full text |Cite
|
Sign up to set email alerts
|

Value and significance of brain radiation therapy during first‐line EGFR‐TKI treatment in lung adenocarcinoma with EGFR sensitive mutation and synchronous brain metastasis: Appropriate timing and technique

Abstract: Background: For lung adenocarcinoma patients with epidermal growth factor receptor (EGFR) sensitive mutation and synchronous brain metastasis (syn-BM), when and how to apply radiotherapy (RT) during first-line tyrosine kinase inhibitor (TKI) treatment remains debatable. Methods: From a real-world multicenter database, EGFR-mutant patients with syn-BM diagnosed between 2010-2020 and treated with first-line TKIs were enrolled and divided into upfront TKI + RT and upfront TKI groups. Median intracranial progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Several studies ( 22 ) believe that SRS combined with targeted therapy should be administered early, which can significantly prolong the prognosis of patients. However, another study by our team ( 23 ) and Chen et al. ( 24 ) showed that, as long as radiotherapy is administered during the course of targeted therapy, the patients’ OS can be prolonged.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies ( 22 ) believe that SRS combined with targeted therapy should be administered early, which can significantly prolong the prognosis of patients. However, another study by our team ( 23 ) and Chen et al. ( 24 ) showed that, as long as radiotherapy is administered during the course of targeted therapy, the patients’ OS can be prolonged.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have indicated that WBRT plus target drugs may have potential survival benefit for improving the treatment response and long‐term survival of NSCLC cases with brain metastasis. 26 However, the conclusion of these studies was different due to the different treatment modalities and clinical heterogeneity of patients. In the present study, we pooled the treatment response and toxicity of the 18 studies included and found the ORR and 1‐year survival rate in the WBRT+TKI group was higher than that of the WBRT only group with a statistical difference ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…There were also meta-analysis that showed that upfront RT including stereotactic radiosurgery (SRS) was associated with better OS and iPFS for EGFR-mutated NSCLC with brain metastases [ 15 , 16 , 17 ]. Some clinical trials draw a conclusion that upfront brain RT based on first-line EGFR-TKIs might improve intra-cranial PFS but not OS in EGFR-mutant lung adenocarcinoma patients with BMs [ 18 , 19 , 20 ]. It is important to note that the radiotherapy technique involved in these studies are predominantly WBRT, whereas SRS is now the primary treatment option for patients with limited brain metastases.…”
Section: Introductionmentioning
confidence: 99%